Study on the propagation probability characteristics and prediction model of meteorological drought to hydrological drought in basin based on copula function - Wang, Huiliang; Zhu, Yujia; Qin, Tianling; Zhang, Xiangyang (Frontiers in Earth Science, 2022)
Studying the probability characteristics of meteorological drought transmission to hydrological drought can help to alleviate drought and optimize the allocation of water resources. This study takes the Yiluo River as the research object, standardized precipitation index SPI and standardized stream flow index SSI were used to represent meteorological and hydrological drought, respectively. Firstly, the stability of the precipitation and stream flow sequence is tested by using the heuristic segmentation algorithm. The correlation between watershed meteorological and hydrological was analyzed using cross wavelet transform and lag correlation to study the transmission time of meteorological drought to hydrological drought. Secondly, the characteristics of watershed drought are discussed by using the travel theory. Finally, the joint distribution of SPI and SSI sequence is constructed using Copula function. From the perspective of conditional probability, the propagation probability and propagation threshold from different levels of meteorological drought to hydrological drought are calculated. Hydrological drought prediction model based on SPI - P(SSI|SPI) relation curve is proposed. The model is also validated based on the historical data. The results show that the model is suitable for the light and middle hydrological drought prediction.